MODEL PEMBINAAN KEAGAMAAN DI ASRAMA BINA SISWA SMA PLUS CISARUA PROVINSI JAWA BARAT - Yusup, Abdurrohman; Suresman, Edi (Universitas Pendidikan Indonesia, 2018)
This research was motivated by the important role of dormitory that wasable to produce the students with many achievements, but there still haveproblems, such as: dating, bulying, and stealing. The purpose of this research is to find out the model of religious guidance at Bina SiswaDormitrory SMA PlusCisarua West Java. This research was conducted with qualitative approach and descriptive case study design. Data collection was done by interview technique, observation, dandocumentation study. The results of this research are: (1) Religious guidance program is divided into two agenda namely daily and weekly activities, (2) The implementation of religious guidance includes the practice of praying congregation, tadarus al-Quran, student lecture, tahajud prayer, muhadhoroh (speech), muhadasah(conversation),tausiyah, guidance of worship, fasting on Monday and Thursday, tahsin, memorizing al-Quran and etc, (3) The religious guidance can increasethe understanding and implementation of religious confidence of the students, and can decline the level of serious violation of students.Penelitian ini dilatarbelakangi oleh peran asrama yang mampu menghasilkan siswa-siswi unggul dan berprestasi, namun di sisi lain masih ditemukan kasus penyimpangan siswa, misalnya berpacaran, bulying, danmencuri. Penelitian ini bertujuan untuk mengetahui model pembinaan keagamaan di Asrama Bina Siwa SMA Plus Cisarua Provinsi Jawa Barat. Penelitian ini dilakukan dengan pendekatan kualitatif dengan desain studi kasus. Pengumpulan data dilakukan dengan teknik wawancara, observasi, studi dokumentasi. Penelitian berkesimpulan bahwa: (1) Pembinaan keagamaan ini mengadopsi sistem kepesantrenan, dengan program kegiatan harian dan mingguan, serta program ekstrakulikuler keagamaan, (2) Pelaksanaan pembinaan keagamaan ini antara lain: shalat berjama’ah, tadarus Al-Qur`an, kultum siswa, shalat tahajud, muhadhoroh (pidato), muhadatsah (percakapan), tausiyah, bimbingan ibadah, puasa Senin-Kamis, tahsin, dan hafalan qur`an, (3) Pembinaan keagamaan tersebut dapat membantu meningkatkan pemahaman dan pengamalan keagamaan siswa, serta menurunkan tingkat pelanggaran berat siswa.